The beauty of the divine: vestments as an ornament in the Christian imaginary - Moreira, Fuviane Galdino (2018)
The clothes of the Christian sculptures are dear to textile studies. Qualified as ornaments by Bonne (1996), the tissues investigated here connect themselves to the traces of the concept of beauty inspired by the Greek antiques. This paper proposes an interpretation about the contact between the History of Sacred Art and the History of Dressing, from the analysis of the dressing modes of two patronesses from Latin America: Our Lady of Angels, from Costa Rica, and Our Lady Mother of Divine Providence, from Porto Rico. Both are objects of our doctoral research. The theory of this study is based on works from the Medieval History that continue reverberating in more recent periods.